Analisis Kesalahan Berbahasa Indonesia Tataran Fonologi Pemelajar BIPA di Alekawa Kota Makassar - Mirnawati, Mirnawati; Usman, Usman; Baharman, Baharman (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
This study aims to describe and analyze the form of Indonesian language errors and their causative factors at the phonological level carried out by BIPA learners in Alekawa, Makassar City. The research data was in the form of oral speech of BIPA learners which contained phonological errors. Data collection was carried out through documentation, observation, and interview techniques. Data is analyzed by the stages of data reduction, data presentation, and conclusion drawn. The results showed significant phonological errors, with the dominant forms of errors including: 1) phoneme changes, such as /a/ to /e/ (e.g. "kalo" to "kelo"), /m/ to /b/ (e.g. "eat" to "bakan"), and /m/ to /ng/ (e.g. "night" to "ngalam"); 2) the omission of phonemes, such as /e/ (e.g. "shoe" becomes "spatu") and /g/ (e.g. "fence" becomes "pair"); and 3) the addition of phonemes, such as /h/, /s/, and /w/ (e.g. "let" become "hayo"). Factors that cause these errors include mother tongue interference due to differences in intonation, syllable, and pressure patterns; lack of mastery of the rules of Indonesian phonology; and age factors that affect the adaptation of the speech organs.